Inovasi Kolaboratif Mahasiswa KKN MB Posko 10 UIN Walisongo dalam Pengembangan Taman Kajera di Kelurahan Jatirejo, Kota Semarang - Erika Ayu Fadhilah; Ida Nurlatifah; Nabila Asla Mufahrida; Naqiya Sabila Elhidaya; M. Yudhis Bayu Laras; Chusnul Adib Achmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to measure the impact of Kajera Park development in Jatirejo Village as part of the KKN MB Posko 10 UIN Walisongo program on community welfare and sustainable development. The research method used interviews and participatory observation by KKN students. The results showed that Kajera Park successfully improved environmental quality and served as a center for inclusive socio-economic activities. The Kajera Thematic Village initiative also developed red ginger-based MSME products that significantly improved the local economy. Despite challenges in terms of funds and manpower, student and community collaboration has proven effective in promoting sustainable development. The Kajera Thematic Village model can be used as a reference for other community development programs in Indonesia.